Restorative Justice in Indigenous Communities as a Path to Contextual Justice - Rahman; Ridwan Fariz Maulana; Rizki Adreni Saragih; Moh Ainul Yakin; Laila Dwi Rohmadhayanti (Jurnal Pelita Raya, 2025)
In an era of decentralisation and strengthening regional autonomy, recognition of the role of indigenous peoples in social governance is becoming increasingly important. This study integrates a community-based restorative justice approach into national legal policy, thereby strengthening efforts to reform the criminal justice system, reducing the burden on law enforcement agencies, and increasing the sense of justice at the grassroots level. This study primarily focuses on integrating relevant theories to construct a comprehensive framework for understanding restorative justice in Indonesian indigenous communities as a form of contextual justice. The results confirm that restorative justice in Indonesian indigenous communities is not merely a traditional legacy, but an intellectual discourse of resistance against the state's monopoly on defining and enforcing justice. Amid national laws that remain colonial in nature, the practice of customary justice shows that true justice arises from the depths of human relationships, not from the rigidity of procedures. The tension between state law and customary law, the decolonial function of restorative justice, and the risk of domestication through institutionalisation all emphasise the need for a paradigm shift in Indonesian law. Thus, the future of justice in Indonesia depends on the state's courage to be the sole centre of legitimacy no longer, but to become a space for dialogue that allows customary justice to grow as an equal partner in upholding humanity and restoring communal life.